An Overview of Systematic Reviews of Chinese Herbal Medicine for Parkinson's Disease - Jin, Xin-Chun; Zhang, Li; Wang, Yong; Cai, Hai-Bo; Bao, Xian-Jun; Jin, You-Yu; Zheng, Guo-Qing (Frontiers in Pharmacology, 2019)
ABSTRACT Parkinson's disease (PD) is a high prevalence neurodegenerative disorder without a disease-modifying therapy. Up to now, a number of systematic reviews have been conducted to evaluate efficacy and safety of Chinese herbal Medicine (CHM) for PD patients. Here, we aimed to assess the methodological quality and reporting quality of systematic reviews using an overview, and then synthesize and evaluate the available evidence level of CHM for PD. Six databases were searched from inception to September 2018. The literatures were selected and data were extracted according to prespecified criteria. A Measurement Tool to Assess Systematic Reviews (AMSTAR) was used to evaluate the quality of methodology, and Grading of Recommendations Assessment, Development and Evaluation (GRADE) to determine the evidence quality of the primary outcome measures. A total of 11 systematic reviews with 230 RCTs of CHM for PD were included. AMSTAR scores of the included reviews were range from 4 to 9. Compared with conventional western medicine (WCM), CHM paratherapy showed significant effect in improving UPDRS score, Webster scale score, PDQ-39, NMSQuest, CHM Syndrome Integral Scale, and PDSS. However, CHM monotherapy showed no difference relative to WCM according to various outcome measures. Adverse events were reported in 9 systematic reviews. The side effect in CHM paratherapy group was generally less than or lighter than that in WCM group. The quality of the evidence of primary outcomes was moderate (42%) to high (54%) according to the GRADE profiler. The present finding supported the use of CHM paratherapy for PD patients but we should treat the evidence cautiously because of the methodological flaws, whereas there is insufficient evidence of CHM monotherapy for PD.